PELAKSANAAN KELAS PARENTING BALAI RW OLEH MAHASISWA MSIB FASILITATOR PUSPAGA KELURAHAN PERAK BARAT - Riska Ayu Rahmaida; Kalvin Edo Wahyudi (Halu Oleo University, 2024)
Violence cases in Surabaya City in 2022 experienced an increase in the number of cases compared to the previous year. The importance of parenting patterns in the family, efforts to fulfill children's rights, and the fact that some families are not harmonious trigger child abuse. This research aims to find out and describe the implementation of the parenting class program at the puspaga Balai RW Kelurahan Perak Barat Surabaya and the role of MSIB students as puspaga facilitators in the implementation of the parenting class program. This research uses qualitative research methods with descriptive research types. The research was analyzed using the theory of parenting program implementation by Asolihin (2013). The results showed that the implementation of the parenting class program at the puspaga RW hall in Perak Barat Surabaya has been running through 3 stages, that is the preparation/planning stage, the implementation stage, and the evaluation and monitoring stage. The role of the puspaga facilitator includes the role of promoter, communicator and companion in the implementation of parenting classes.